Wage bargaining institutions – from crisis to crisis - Visser, Jelle (Luxembourg, 2013)
"This essay reviews half a century of developments in bargaining coverage, the structure of bargaining, and bargaining coordination respectively in thirty countries, with an emphasis on the last twenty years. Under coverage or the extent of collective bargaining and pay setting, the connection with union density, employer organization, and administrative extension is analysed. In the section on bargaining structure the main issues are decentralisation, multi- or single-employer bargaining, the level at which most bargaining takes place, the organization or articulation of multi-level bargaining, and the existence and use of opening clauses. The discussion of coordination includes an attempt to identify different mechanisms through which wage leadership may be established, varying from state controls to social pacts, and from associational controls to trend- or pattern setting behaviour."